2016
DOI: 10.1038/srep20380
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state optical refrigeration to sub-100 Kelvin regime

Abstract: Since the first demonstration of net cooling twenty years ago, optical refrigeration of solids has progressed to outperform all other solid-state cooling processes. It has become the first and only solid-state refrigerator capable of reaching cryogenic temperatures, and now the first solid-state cooling below 100 K. Such substantial progress required a multi-disciplinary approach of pump laser absorption enhancement, material characterization and purification, and thermal management. Here we present the culmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 15 publications
0
113
0
Order By: Relevance
“…We used the YLF:10%Yb laser-cooling crystal that was cooled to 91 K in a previous study 10 . This  crystal was cut so that the linearly polarized pump laser has because the absorption cross section of the E4→E5 crystal-field transition in a YLF:Yb crystal at 1020 nm is ~1.7× greater in this geometry than that with polarization 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the YLF:10%Yb laser-cooling crystal that was cooled to 91 K in a previous study 10 . This  crystal was cut so that the linearly polarized pump laser has because the absorption cross section of the E4→E5 crystal-field transition in a YLF:Yb crystal at 1020 nm is ~1.7× greater in this geometry than that with polarization 12 .…”
Section: Methodsmentioning
confidence: 99%
“…However, laser cooling of Yb 3+ -doped solids to cryogenic temperatures is only practical if η ext η abs exceeds 0.98–0.99, a challenging requirement that necessitates a cooling crystal with exquisite purity 9 . High-purity YLiF 4 crystals doped with 10 mol% Yb 3+ (YLF:10%Yb) have recently been cooled to 91 K by exciting them with a laser tuned to the E4→E5 crystal-field transition of Yb 3+ at 1020 nm 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they reported that Yb 3+ :YLF bulk crystals can be cooled in vacuum to 91 K from room temperature with tuning the excitation of the crystal to Yb 3+ E 4 ‐E 5 resonance at 1020 nm, shown in Figure . The energy levels of Yb 3+ are shown in Figure b …”
Section: Photothermal Coolingmentioning
confidence: 99%
“…(Inset) Illustration of the cooling cavity, which enables multiple passes of the cooling laser through the crystal. (b) The crystal temperature (blue) reaches 91 K after ≈ 12 minutes of pumping while the clamshell temperature is maintained at ≈ 265 K. Figure reproduced with permission from reference copyright Nature Publishing Group.…”
Section: Photothermal Coolingmentioning
confidence: 99%
See 1 more Smart Citation